When the textbook is not enough: How to shape an ELF classroom? - Guerra, Luis (2019)
This chapter is devised for English language teaching (ELT) practitioners to reflect on how language and culture are portrayed in English as a Foreign Language (EFL) textbooks, and explore how an English as a Lingua Franca (ELF) approach can be further integrated into their teaching practices through supplementary activities and teaching materials. The target audience is pre-service and in-service teachers as well as course-book designers. After reading the chapter, readers will be informed of several ELF-related teaching activities and materials that focus both on language and culture, so that they could explore and apply them in their teaching contexts.